Lipidomic analysis of serum from horses with strongyle infection - Lamb, Jenna; Hallowell, Gayle D.; Harris, Patricia; Xing-Quan, Zhu; Elsheikha, Hany M. (OMICS Publishing Group, 2012)
The development of techniques capable of accurate diagnosis of strongyle infections is at the forefront of research in equine parasitology. The aim of this study was to evaluate the potential, for using lipidomics in the diagnosis of strongyle infection. Blood and fecal samples were collected from 30 horses. Fecal egg count (FEC) results were used to select the serum samples from six uninfected horses (negative controls) and from the five horses with the highest burdens. The lipid portion of serum samples was extracted and analyzed using High Performance Liquid Chromatography-Mass Spectroscopy. The concentrations of 66 lipid metabolites differed between infected and uninfected horses (p<0.025). Database comparison of mass/charge (m/z) ratios and retention times were used to tentatively identify 16 of these metabolites. The roles of these metabolites and reasons for the observable changes were discussed. These results demonstrate the potential for the use of high resolution lipidomic analysis, for the development of a diagnostic technique capable of detecting, and perhaps stratifying, equine strongyle infection.